LiNbO3 dispersive filter with fan-shaped transducers and reflective arrays - VIKTOROV, P. V.; ZHEZHERIN, A. R.; KONOVALOVA, L. P. (Archives of Acoustics, 1991)
At present, dispersive devices with reflective arrays (RAC) are used for radiosignal processing. RAC with unidistant transducers and U-path of acoustic waves with dispersive slanted transducers and slanted reflective arrays (RA) described in literature, have rather high interreflections in RA. This affects the pulse of a device. In the presented work, RAC with fan-shaped transducers (FST) and slanted RA is described. An analysis of the amplitude distribution of the FST acoustic field and the dependence of the maximum of the distribution in FST aperture on instantaneous frequency are presented. Basing on this analysis and the type of the dispersive characteristic of a device, the relations for RA parameters are obtained. The parameters of the prototypes fabricated of the YZ-LiNbO3 piezosubstrate are presented. An analysis of the results obtained is performed.